HUBUNGAN PENGGUNAAN KB IUD DENGAN EROSI PORSIO DI POLI KB DAN KANDUNGAN RSUP NTB TAHUN 2012-2013 - Ni Putu Karunia Ekayani (Jurnal Kesehatan Prima, 2014)
Abstract: Background: Family Planning programs in Indonesia have been admitted both nationally and internationally to be successful programs in decreasing birth rate. The number of contraceptive acceptors is increasing and it reflects that Family Planning programs have became the society's need. Use of contraception of IUD counted 746.702.  One of  the effect  use of IUD is  Erosion of Porsio. Proporsi erosion of Porsio in RSUP NTB  was 116 aceptor. Objectives: The purpose of the study is  to fine out the correlation between  contraception  IUD  and  Erosion of Porsio. Methods: This was an  analityc study using cross-sectional. The sampel of the study were 332 aceptor  in Poli  KB and Kandungan RSUP NTB 2012-2013. Samples were taken through simple random sampling The data analysis used were univariable with frequency distribution and  bivariable with chi-square. Results: The Result of research indicate that from 332 sampel, using IUD 50%, erosion of porsio counted 10,5% and Early weaning had a significant corelation with use of IUD with Erosion of porsio (p= 0,000) From the result of the study, it could be concluded that used of IUD corelation with Erosion of porsio.